Cost-Benefit Analyses of Pekin Duck Fattening According to Various Housing Systems and Slaughter Age - Demir, Pinar; Erisir, Zeki; Poyraz, Oeznur; Onbasilar, Esin Ebru; Erdem, Evren (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
This research was carried out to determine the effects of various housing systems and slaughter age of Pekin ducks on profitability. In this research, it was determined that semi intensive pool system had positive effects on ducklings' welfare in production; on the other hand profitability of duck production is much higher in semi intensive systems without pool.
Farklı barındırma sistemleri ve kesim yaşına göre pekin örde?i besisinin fayda-maliyet analizi
Keywords: Pekin duck; Various housing systems; Profitability; Cost